2019
DOI: 10.1007/s00253-019-09689-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Oenococcus oeni populations in natural habitats

Abstract: Oenococcus oeni is the lactic acid bacteria species most commonly encountered in wine, where it develops after the alcoholic fermentation and achieves the malolactic fermentation that is needed to improve the quality of most wines. O. oeni is abundant in the oenological environment as well as in apple cider and kombucha, whereas it is a minor species in the natural environment. Numerous studies have shown that there is a great diversity of strains in each wine region and in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 84 publications
1
27
0
2
Order By: Relevance
“…cabbage, radish). Similarly, O. oeni and L. lindneri have only been detected in relatively high abundance in fermented beverages (wine and beer, specifically) and not on plant tissues (Liu et al ., ,b; Lorentzen and Lucas, ).…”
Section: Specialist Plant‐associated Labmentioning
confidence: 99%
“…cabbage, radish). Similarly, O. oeni and L. lindneri have only been detected in relatively high abundance in fermented beverages (wine and beer, specifically) and not on plant tissues (Liu et al ., ,b; Lorentzen and Lucas, ).…”
Section: Specialist Plant‐associated Labmentioning
confidence: 99%
“…Increasing interest has been direct to the understanding of the interactions between S. cerevisiae [24][25][26] and non-Saccharomyces [27][28][29][30] strains with different lactic acid bacteria (LAB), such as L. plantarum [5,31]. However, none of the above studies has tested the relation among the above three microbes by carrying out the vinification at the industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…Group B and C strains have been isolated from wine and cider, while group A contains only wine strains, suggesting they are the best adapted to wine. IOEBS277 and S25 were shown to belong to different subgroups in the phylogroup A (27,57).…”
Section: Methodsmentioning
confidence: 98%
“…Alternately, we also used the nonlysogenic host strain O. oeni S25, which was also found to be phage sensitive in earlier studies (20). Previous population structure analyses based on multilocus sequence typing (MLST) of strains from diverse products (wines, ciders, and kombucha) and geographic origins have revealed that O. oeni consists of four genetic groups of strains (A to D) (27,56,57). Group D comprises all five strains recently isolated from kombucha.…”
Section: Methodsmentioning
confidence: 99%